Intellectual disability associated with craniofacial dysmorphism, cleft palate, and congenital heart defect due to a de novo MEIS2 mutation: A clinical longitudinal study. Issue 4 (11th January 2021) - Gangfuß, Andrea; Yigit, Gökhan; Altmüller, Janine; Nürnberg, Peter; Czeschik, Johanna Christina; Wollnik, Bernd; Bögershausen, Nina; Burfeind, Peter; Wieczorek, Dagmar; Kaiser, Frank; Roos, Andreas; Kölbel, Heike; et al.
Abstract: Intellectual disability (ID) has an estimated prevalence of 1.5%–2%. Whole exome sequencing (WES) studies have identified a multitude of novel causative gene defects and have shown that sporadic ID cases result from de novo mutations in genes associated with ID. Here, we report on a 10‐year‐old girl, who has been regularly presented in our neuropediatric and genetic outpatient clinic. A median cleft palate and a heart defect were surgically corrected in infancy. Apart from ID, she has behavioral anomalies, muscular hypotonia, scoliosis, and hypermobile joints. The facial phenotype is characterized by arched eyebrows, mildly upslanting long palpebral fissures, prominent nasal tip, and large, protruding ears. Trio WES revealed a de novo missense variant in MEIS2 (c.998G>A; p.Arg333Lys). Haploinsufficiency of MEIS2 had been discussed as the most likely mechanism of the microdeletion 5q14‐associated complex phenotype with ID, cleft palate, and heart defect. Recently, four studies including in total 17 individuals with intragenic MEIS2 variants were reported. Here we present the evolution of the clinical phenotype and compare with the data of known individuals.